2015
DOI: 10.1002/sm2.78
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Predictors of Sexual Dysfunction in Men on Active Surveillance for Prostate Cancer

Abstract: AimThe aim of this study was to examine the relationship between sexual dysfunction, repeat biopsies and other demographic and clinical factors in men on active surveillance (AS).MethodsPatient-reported outcomes (PROs) measures were administered at enrollment and every 6 months to assess quality of life (QOL), psychosocial and urological health outcomes. Using mixed-effects models, we examined the impact of repeat biopsies, total number of cores taken, anxiety, age, and comorbidity on sexual function over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 33 publications
1
40
1
3
Order By: Relevance
“…The increase in AS patients' generalized anxiety symptoms over time contradicts previous research that reported declining anxiety in this group . Much of international AS research has been conducted on men being managed in centers with a strong focus on AS who have been refining and perfecting the diagnosis experience for almost two decades, and therefore AS is more widely accepted by clinicians and patients .…”
Section: Discussionmentioning
confidence: 68%
“…The increase in AS patients' generalized anxiety symptoms over time contradicts previous research that reported declining anxiety in this group . Much of international AS research has been conducted on men being managed in centers with a strong focus on AS who have been refining and perfecting the diagnosis experience for almost two decades, and therefore AS is more widely accepted by clinicians and patients .…”
Section: Discussionmentioning
confidence: 68%
“…Neither erectile function nor sexual activity status was associated with number of PBs [10]. In a longitudinal work of Sahane M. Pearce et al [11] were evaluated 195 patients during the first 24 months of active surveillance, highlighting a decline in sexual function. Men experienced decreased sexual function and a decline in PCa anxiety over the first 24 months of enrollment on an AS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety, other comorbid conditions, the number of cores, and the number of biopsies were not associated with declining sexual function in their study. Sexual function in men undergoing AS is multifactorial and is influenced by many factors including age, aging over time and comorbid conditions rather than increased biopsy exposure [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, these factors have already been mentioned as risk factors by Pearle et al as well as in the EAU Guidelines on Erectile Dysfunction [6,7].…”
Section: Letter To Editormentioning
confidence: 99%
“…According to PRIAS study, this anxiety decreases after 18 months of AS [5]. Considering the cooccurrence of ED with anxiety, ED is rather an early problem of AS and this topic is already covered by Pearce et al but using different parameters for erectile function assessment [6]. Quaresima et al preferred the IIEF-5 questionnaire, which provided high sensitivity and specificity and is recommended by the European Association of Urology (EAU) Male Sexual Dysfunction Guidelines [7,8].…”
Section: Letter To Editormentioning
confidence: 99%